Formulasi masker wajah serbuk nano teh celup bekas dan aktivitas antibakteri terhadap Propionibacterium acnes dan Staphylococcus epidermidis - Matondang , Fikriyah Hafni; Lubis, Minda Sari; Yuniarti , Rafita; Rani, Zulmai (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The increase in the cosmetic industry has caused a variety of facial mask products to circulate on the market, making it difficult for consumers to find one that suits their skin condition. Masks from well-known brands are easy to get, but some cause skin problems. Since ancient times, Indonesians have used plants as medicines and cosmetic ingredients for skin care. Tea can be processed into new active ingredients such as antioxidants, antibacterials, and anti-aging for cosmetics. Nanoparticle-based cosmetics are superior to micro-scale cosmetics. The objective of the research was to determine whether used tea bag powder meets the characteristic requirements as nanopowder, to determine whether used tea bag nanopowder in facial mask preparations meets the physical quality requirements, and to determine whether used tea bag nano powder facial mask preparations has antibacterial activity against Propionibacterium acnes and Staphylococcus epidermidis. This research method was true experimental with post test only control group design research design. The independent variables are tea bag powder and nanopowder and powder face mask formulation variations. The dependent variables are the characteristics of the simplicia, secondary metabolites, nanopowder characteristics, powder face mask formulation, and antibacterial activity test. The results showed that tea bag powder and nanopowder contained alkaloid, steroid, flavonoid, saponin, and tannin compounds. The inhibitory activity of the used tea bag nano powder mask on Propionibacterium acnes was 11.3 mm on Staphylococcus epidermidis, which was 11.2 mm. The tea bag powder used meets the characteristics of a nanopowder with a particle size of 684 nm. I used a tea bag nanopowder to prepare a face mask that meets the physical quality requirements.